2021
DOI: 10.1038/s41467-021-21692-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete biosynthesis of a sulfated chondroitin in Escherichia coli

Abstract: Sulfated glycosaminoglycans (GAGs) are a class of important biologics that are currently manufactured by extraction from animal tissues. Although such methods are unsustainable and prone to contamination, animal-free production methods have not emerged as competitive alternatives due to complexities in scale-up, requirement for multiple stages and cost of co-factors and purification. Here, we demonstrate the development of single microbial cell factories capable of complete, one-step biosynthesis of chondroiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 54 publications
0
29
2
1
Order By: Relevance
“…Those authors showed that the glycosylated and non-glycosylated forms of the enzyme had similar activities. More recently, the soluble expression of human C4OST enzyme was also achieved in E. coli K4 and in E. coli K-12 MG1655 [160] .…”
Section: Enzymatic and Chemoenzymatic Cs Productionmentioning
confidence: 99%
“…Those authors showed that the glycosylated and non-glycosylated forms of the enzyme had similar activities. More recently, the soluble expression of human C4OST enzyme was also achieved in E. coli K4 and in E. coli K-12 MG1655 [160] .…”
Section: Enzymatic and Chemoenzymatic Cs Productionmentioning
confidence: 99%
“…In another example, the production of more complex sulfated glycosaminoglycans was engineered into E. coli . To this aim, the Koffas group introduced three metabolic pathways into cells to produce the three required components of chondroitin sulfate synthesis — chondroitin, a sulfate donor, and a sulfotransferase [ 58 ]. This study provides a simple synthesis route as an alternative to the conventional isolation of chondroitin sulfate from animal tissues.…”
Section: Engineering Cells To Synthesize (Precursors Of) Non-living Materialsmentioning
confidence: 99%
“…Therefore, in the past few years research efforts have been focused on the improvement of the production process, as well as on the design of better heterologous hosts to produce GAGs. Recent advances in the microbial production of GAGs using non-pathogenic hosts (mostly prokaryotic organisms) have been reported [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%